PENGEMBANGAN THULU ZAMAN DALAM ACCELERATED LEARNING DI PONDOK PESANTREN MAKTUBA AL-MAJIDIYAH PEMEKASAN - Khalilurrahman , M.; Gaffar, Abdul (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2023)
The organization of an institution that is short and commercial will affect the teaching and learning process of students, especially in character formation, which requires a long life (long life education) in creating the nation's generation. The research results found that the ancient era model according to Az-Zarnuji at the Maktuba Islamic Education Institute was divided into three research results: first, long time, quality of time, and target achievement. Second, in the past, according to Az-Zarnuji at the Maktuba Al-Majidiyah Palduding Pamekasan Islamic boarding school, it was implemented in two aspects, always guided by methods and clever use of time. Third, supporting and inhibiting factors for past development in accelerated learning include the completeness of teaching and learning facilities, the activeness and skills of teachers/supervisors, the formation of study groups, and control from supervisors; as well as differences in student backgrounds, method inconsistencies, and time-intensive activities.